SOCIAL PERMISSIVE REASONING AS INHERITED POVERTY (CRITICAL VIEW OF A POLITICAL DYNASTY PRONE TO CORRUPTION) - Amalia Syauket; Nina Zainab (Lex LATA, 2019)
Political Dynasty and Corruption are like two inseparable things. In Indonesia, political dynasty has been growing since the era of reformation, right after the implementation of regional autonomy system which enables the continuation of local politics succession directly. At 2018 regional election, there were five provinces with candidates from political dynasties such as: Banten, South Sumatera, West Java, East Java, and West Kalimantan.As a causality relation, corruption is the outcome and permissive behavior is the cause. In the Province of Banten, corruption occurs due to the permissive behavior stemmed socially ad structurally in the society. One of the influence of the permissive behavior towards corruption is the level of education. The lower it is, the higher the level of poverty, thus more permissive they are towards corruption, as well as the society’s lack of knowledge about negative effects of political dynasty. The people in Banten seems don’t fully acknowledge that political dynasty is degrading the essence of democracy and prone to corruption practice. In 2016, Banten helds sixth position in Indonesia in their level of poverty, and the second lowest in Java. Based on statistical data, until 2017 the amount of people with poverty in the cities and rural areas has increased.This research used qualitative research method in explanative manner, where the target of this research was to explain the social permissive reasoning phenomenon in the society of Banten as an inherited poverty of a political dynasty which prone to corruption, with several facts that supported data and research analysis which can be used to understand issues derived from such phenomenon.